Running stride length and rate are changed and mechanical efficiency is preserved after cycling in middle-level triathletes - Gomes da Rosa, R.; Bianchi de Oliveira, H.; Ardigò, L. P.; Gomeñuka, N. A.; Fischer, G.; Peyré-Tartaruga, L. A. (Scientific Reports, 2019)
Although cycling impairs the subsequent metabolic cost and performance of running in some triathletes, the consequences on mechanical efficiency (Eff) and kinetic and potential energy fluctuations of the body center of mass are still unknown. The aim of this study was to investigate the effects of previous cycling on the cost-of-transport, Eff, mechanical energy fluctuations (Wtot), spring stiffness (Kleg and Kvert) and spatiotemporal parameters. Fourteen middle-level triathletes (mean ± SD: maximal oxygen uptake, VO2max = 65.3 ± 2.7 ml/kg.min, age = 30 ± 5 years, practice time = 6.8 ± 3.0 years) performed four tests. Two maximal oxygen uptake tests on a cycle ergometer and treadmill, and two submaximal 20-minute running tests (14 km/h) with (prior-cycling) and without (control) a previous submaximal 30-minute cycling test. No differences were observed between the control and post-cycling groups in Eff or Wtot. The Eff remains unchanged between conditions. On the other hand, the Kvert (20.2 vs 24.4 kN/m) and Kleg (7.1 vs 8.2 kN/m, p < 0.05) were lower and the cost-of-transport was higher (p = 0.018, 3.71 vs 3.31 J/kg.m) when running was preceded by cycling. Significantly higher stride frequency (p < 0.05, 1.46 vs 1.43 Hz) and lower stride length (p < 0.05, 2.60 vs 2.65 m) were observed in the running after cycling condition in comparison with control condition. Mechanical adjustments were needed to maintain the Eff, even resulting in an impaired metabolic cost after cycling performed at moderate intensity. These findings are compatible with the concept that specific adjustments in spatiotemporal parameters preserve the Eff when running is preceded by cycling in middle-level triathletes, though the cost-of-transport increased.